Magnetic separation of oxygen carriers from bed ash in heat and power plants - Karlsson, Frida (My University, 2019)
In response to climate change, research is currently conducted on the possibility of reducing the CO2 emissions from combustion plants. Technologies utilizing uidized beds can be used for combustion with low emissions. Chemical-looping combustion (CLC) and oxygen carrier aided combustion (OCAC) are two such technologies, using uidized beds with an oxygen-carrying bed material, which can be used instead of sand to transport oxygen between air and fuel. To minimize resource use and costs, it is important to reuse spent oxygen carriers. The possibility of recycling and reusing these oxygen carriers is studied in this work by separating the metal-based oxygen carriers from fuel ash through magnetic separation, and is based on the results of a previous Bachelor thesis project conducted in 2018. In this thesis, the magnetic properties of three oxygen carrier materials, ilmenite, LS Slag and Sibelco Calcined, that have been used in combustion processes are investigated using di erent characterization techniques. This is done in order to obtain a better understanding of the mechanisms which govern the magnetic behavior of oxygen carrier materials. Of the investigated materials, ilmenite and LD Slag are iron-based and Sibelco Calcined is manganese-based. Correlations between data from magnetic separation of these materials obtained in the Bachelor thesis and data obtained in this project are investigated. Di erent experimental techniques were employed, including measurements of magnetic susceptibility, X-ray powder di raction (XRD) and scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX). The possibility to create a model by which the magnetic fraction can be predicted is further explored. The results indicate that there is some correlation between magnetic susceptibility and the obtained magnetic fraction, though not to the extent that would be needed in order to create a model. The results further suggest that the iron-oxide magnetite (Fe3O4), common in the iron-based oxygen carriers, is signi cant to the magnetic separability of these oxygen carrier materials. An oxygen carrier based on manganese ores could still be separated through magnetism, although this will likely depend upon the amount of iron in the sample. Suggestions can be made to use manganese ores with high concentrations of iron, as this is indicated to increase the magnetic properties of the material.
Keywords: Chemical-looping combustion, circulating uidized bed, oxygen-carrier aided combustion, oxygen carrier, carbon capture and storage, ilmenite, LD Slag, manganese ore, magnetic susceptibility, magnetic separation